Media Development Theory and Learning Resources for MI/SD Level - Hijriayani, Wulan; Alfiandi, M. Hafiz; Harahap, Desmidar (Jurnal Riset Ilmu Pendidikan, 2025)
The development of instructional media and learning resources is a crucial aspect in improving the quality of education, especially at the elementary level, including Madrasah Ibtidaiyah (MI) and Sekolah Dasar (SD). This study aims to explain the foundational theories underlying the development of instructional media and learning resources, as well as their application in primary education. A descriptive qualitative approach is used, relying on literature review to explore relevant theories and frameworks. Educational communication theory, cognitive, constructivist, and behaviorist learning theories are presented as the basis for media development. Furthermore, development models such as ADDIE, ASSURE, and Dick & Carey are discussed as systematic approaches for designing effective learning media. The findings indicate that media and resources developed with consideration of the learners’ characteristics, learning context, and technological integration can enhance student engagement, comprehension, and motivation. This study is expected to provide conceptual guidance for teachers, media developers, and policymakers in creating creative, enjoyable, and meaningful learning environments at the elementary level.